Analisis Kesulitan Kognitif Siswa Sekolah Dasar dalam Memahami Materi Ekosistem pada Pembelajaran IPA - Marsela Manuru Kuroru; Nur Rahmah (Universitas Cokroaminoto Palopo, 2023)
The learning process often involves students who still have difficulty understanding the material which has an impact on learning outcomes. Students find it difficult to learn when the content they are learning has complex concepts. Ecosystem is one of the natural science subjects in elementary schools where students still have difficulty meeting learning objectives. Student learning outcomes in ecosystem material showed that 52% of the students scored in the moderate category and 14% of the students scored in the very low category. The problem in this study is how the cognitive difficulties of class V students at SDN 6 Palu in understanding material related to ecosystems. The purpose of this study was to analyze students' cognitive difficulties in understanding the ecosystem concept. The research samples were 29 students and 1 science teacher. Data collection methods used include questionnaires, interviews, and learning outcomes documents. In addition, data analysis was carried out through 4 stages, namely data collection, data compaction, data compilation and drawing conclusions. The findings of this study indicate that some students have difficulty understanding concepts related to ecosystems due to attention disturbances such as difficulty concentrating, difficulty remembering material and difficulty maintaining movement control or hyperactivity while studying.